Die Lehnwörter im Wortschatz der spätbyzantinischen historiographischen Literatur - Zervan, Vratislaw (2019)
This volume examines the loanwords found in 18 late-Byzantine histories and chronicles. In order to analyze the lexical interferences in the lexicon of late-Byzantine historical literature, all words were included (except place names and proper names) that substantiate language contact. The editors place special emphasis on the sociolinguistic context in which the loanwords were used.